Protests and riots that changed America - Stoltman, Joan (American history (Lucent Books), 2019)
Examines a variety of protests and riots that impacted American history over the years ranging from Shays's Rebellion in 1786 to civil rights and war protests. Includes resources for further information and color photographs.